Diagnosis and management of giant cell arteritis: an Asia‐Pacific perspective. (17th April 2018) - Ninan, Jem V.; Lester, Susan; Hill, Catherine L.
Abstract: Giant cell arteritis is the commonest primary vasculitis of the elderly. However, the prevalence does vary widely between populations with highest incidence amongst Northern Europeans and lowest amongst East Asians. Preliminary studies suggest that clinical manifestations may differ between different populations. Newer diagnostic approaches including ultrasound, MR angiography and PET imaging are under review. While there have been recent advances in the diagnosis of GCA particularly with regard to imaging, there is an urgent need for improvements in methods of diagnosis, treatment and requirement for screening. Glucocorticoid treatment remain the backbone of therapy. However, glucocorticoid therapy is associated with significant adverse effects. Conventional and novel immunosuppressive agents have only demonstrated modest effects in a subgroup of steroid refractory GCA due to the different arms of the immune system at play. However, recently a study of IL‐6 blockade demonstrated benefit in GCA. Newer approaches such as fast‐track pathways can also result in improvements in consequences of GCA including blindness.